Evaluating The Effectiveness of Oral Health Promotion Package (OHPP) on Oral Hygiene, Oral Halitosis, and Gingivitis Among 6-18 Years Old Children Residing in Two Orphanges in Coimbatore City, India: Interventional Study - Bhuvaneshwari S 21D08101; Dr. Chandrashekar B. R (JSS AHER,Mysuru JSSDCH, Mysuru, 2021)
1. Introduction 2. aims and Objectives 3. Review of literature 4. Methodology 5. Results 6. Discussion 7. strength and Limitations 8. Conclusion 9. References 10.Annexures